Comparative Analysis of 30-Day Readmission, Reoperation, and Morbidity Between Lumbar Disc Arthroplasty Performed in the Inpatient and Outpatient Settings Utilizing the ACS-NSQIP Dataset. Issue 5 (June 2021) - Katz, Austen David; Perfetti, Dean Cosmo; Job, Alan; Willinger, Max; Goldstein, Jeffrey; Kiridly, Daniel; Olivares, Peter; Satin, Alexander; Essig, David
Study Design: Retrospective cohort study. Objective: Spine surgery has been increasingly performed in the outpatient setting, providing greater control over cost, efficiency, and resource utilization. However, research evaluating the safety of this trend is limited. The objective of this study is to compare 30-day readmission, reoperation, and morbidity for patients undergoing lumbar disc arthroplasty (LDA) in the inpatient versus outpatient settings. Methods: Patients who underwent LDA from 2005 to 2018 were identified using the ACS-NSQIP (American College of Surgeons National Surgical Quality Improvement Program) database. Regression was utilized to compare readmission, reoperation, and morbidity between surgical settings, and to evaluate for predictors thereof. Results: We identified 751 patients. There were no significant differences between inpatient and outpatient LDA in rates of readmission, reoperation, or morbidity on univariate or multivariate analyses. There were also no significant differences in rates of specific complications. Inpatient operative time (138 ± 75 minutes) was significantly ( P < .001) longer than outpatient operative time (106 ± 43 minutes). In multivariate analysis, diabetes ( P < .001, OR = 7.365), baseline dyspnea ( P = .039, OR = 6.447), and increased platelet count ( P = .048, OR = 1.007) predicted readmission. Diabetes ( P = .016, OR = 6.533) and baseline dyspnea ( P = .046, OR = 13.814) predicted reoperation. Baseline dyspnea ( P = .021, OR = 8.188) and ASA (American Society of Anesthesiologists) class ≥3 ( P = .014, OR = 3.515) predicted morbidity. Decreased hematocrit ( P = .008) and increased operative time ( P = .003) were associated with morbidity in univariate analysis, but not in multivariate analysis. Conclusions: Readmission, reoperation, and morbidity were statistically similar between surgical setting, indicating that LDA can be safely performed in the outpatient setting. Higher ASA class and specific comorbidities predicted poorer 30-day outcomes. These findings can guide choice of surgical setting given specific patient factors.